Envelhecimento e pobreza: o idoso do distrito de M Boi Mirim - Almeida, Vanessa Lopes de (2013)
The aging process and poverty as a form of violence against the elderly in the districts of Jardim Angela and Jardim São Paulo (South Zone of São Paulo) is the subject of this current dissertation. This study aims to understand two aspects: not only daily life of elderly from outskirt of Sao Paulo and their desires, difficulties and achievements, but also exploring the various forms of violence suffered by elderly, among which, the moral, social and institutional violence. The investigation focus is elderly assisted and accompanied by the Reference Center for Social Assistance (CRAS M´BOI MIRIM). Eldery who seeks this CRAs by their own initiatives or are accompanied by technical team due to prosecutor complaints and subsequent request of visit from Judiciary of the São Paulo. This dissertation intends to understand the processes experienced by elderly and forms of violence little visualized. I have considered elderly do not get mobility between social classes and do not increase their power of consumption and elderly that integrate a group which grows sharply, sometimes on account of omission of the State, or due to omission of family to look after them, because of the family don´t provide them proper care, this circumstances generate numerous abuses. For development of this research, We have adopted methodological procedure of Oral History of life for men and women 60 to 80 years monitored by CRAS, specifically elderly whose income tax from zero to a minimum wage, including retirees, pensioners and people who receive social assistance BPC (LOAS). All user has surveyed were referenced by CRAS M BOI MIRIM from September 2011 to September 2012